On Roots and Nature of the Normative Regulation of the Criminal Offence of Theft in the Tradition of Tsar Dušan Legislation - Vujović, Ognjen B. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
In this paper the comparison between several norms of the Criminal Offence of Theft in the tradition of Tsar Dusan legislation and certain provisions of the Roman law was performed. On this occasion, the issue of robbery, theft of fruits and complicity to theft were treated in particular.
Keywords: complicity to theft; robbery; furtum; Iustinian code; Code of Emperor Dušan